Clinical outcomes of endoscopic submucosal dissection for superficial esophageal neoplasms extending to the cervical esophagus - Ariyoshi, Ryusuke; Toyonaga, Takashi; Tanaka, Shinwa; Abe, Hirofumi; Ohara, Yoshiko; Kawara, Fumiaki; Ishida, Tsukasa; Morita, Yoshinori; Umegaki, Eiji; Azuma, Takeshi (Endoscopy, 2018)
Background The feasibility and safety of endoscopic submucosal dissection (ESD) for superficial esophageal neoplasms extending to the cervical esophagus currently remain unknown because of the limited number of cases. We aimed to clarify the clinical outcomes of these cases.Methods This was a case series study conducted at a single institution that enrolled 26 consecutive patients with superficial esophageal neoplasms extending to the cervical esophagus who underwent ESD between July 2003 and December 2015.Results En bloc and complete resection rates were both 100 % and no major intraprocedural complications occurred. Thirteen patients were treated with prophylactic steroid therapy. The incidence of postoperative stricture in patients with a circumferential mucosal defect of more than three-quarters was 72.7 %. Four patients required entire circumferential resection, with perforation occurring after endoscopic balloon dilation (EBD) in two and EBD being required for more than 1 year in the other two. Conclusions ESD including the cervical esophagus is technically feasible. Circumferential resection may cause refractory postoperative stricture or post-EBD perforation, so needs to be avoided where possible.